Optimal Stereoacuity Reveals More Than Critical Time in Patients With Intermittent Exotropia - Wu, Haoran; Li, Xiaoning; Tang, Yao; Xu, Qinglin; Zhang, Xuhong; Zhou, Lu; Lan, Weizhong; Zhang, Bin; Yang, Zhikuan (Frontiers in Neuroscience, 2020)
Background: Despite the periodic misalignment of two eyes, some intermittent exotropia (IXT) patients exhibit normal stereoacuity, particularly when evaluated with static tests. It is not clear if the temporal integration process of stereopsis is altered in IXT patients, thus warranting further research. Methods: IXT patients (n = 29) and age-matched normal controls (n = 36) were recruited. Static stereopsis was measured with the Titmus stereoacuity test. In computer-generated random dots tests, stereoacuity was measured with a stimuli presentation duration varying from 100 to 1,200ms. And the relationship between stereoacuity and stimuli duration was fitted into a quadratic model. Optimal stereoacuity was achieved when fitted curve flattened and the critical integration time was the duration needed to achieve optimal stereoacuity. Results: IXT patients were not found to differ significantly from control subjects under the Titmus test, while the Random Dots stereotest showed significantly worse optimal stereoacuity and significantly longer critical integration time. Multiple regression analysis showed that age (R=-4.83; P=0.04) had statistically significant negative correlation on the critical integration time, age (R=-6.45; P=0.047) and exotropia control scores (R=60.71; P=0.007) had statistically significant effects on optimal stereoacuity. Conclusions: The temporal integration for stereopsis is impaired in IXT patients, requiring longer critical integration time to achieve elevated optimal stereoacuity.